Radicalism in Islam resurgence and ramifications - Mohanty, Nirode (University Press of America, 2012)
Radicalism in Islam explores the causes of Islamic terrorism, the resurgence of radicalism, the global jihad of radical Islamists, and the impact of new technology on terrorism, including new deadly threats to information and environmental systems. The book includes: Views of Muslim scholars both for and against jihad and perspectives of terrorism experts; An analytical approach including systems engineering; Empirical data on economics, energy, trade, globalization, religion, and immigration.